'Sneezing' plants: pathogen transport via jumping-droplet condensation. Issue 155 (19th June 2019) - Nath, Saurabh; Ahmadi, S. Farzad; Gruszewski, Hope A.; Budhiraja, Stuti; Bisbano, Caitlin E.; Jung, Sunghwan; Schmale, David G.; Boreyko, Jonathan B.
Abstract : We show that condensation growing on wheat leaves infected with the leaf rust fungus, Puccinia triticina, is capable of spontaneously launching urediniospores off the plant. This surprising liberation mechanism is enabled by the superhydrophobicity of wheat leaves, which promotes a jumping-droplet mode of condensation powered by the surface energy released from coalescence events. We found that urediniospores often adhere to the self-propelled condensate, resulting in liberation rates of approximately 10 cm −2 h −1 for leaves infected with rust. Urediniospores were catapulted up to 5 mm from the leaf's surface, a distance sufficient to clear the laminar boundary layer for subsequent dispersal even in gentle winds.